Cambio climático y agricultura: una revisión de la literatura con énfasis en América Latina - Alejandro J. López Feldman; Danae Hernández Cortés (El Trimestre Económico)
The increment in greenhouse gas emissions and its effect on climate is such that the need for the agricultural sector to adapt seems inevitable. However, given that adaptive measures are limited, it is possible that climate change will affect food availability and increase price volatility. This essay presents a synthesis of the evi- dence of the effects that climate change has on the agricultural sector, with a special emphasis on Latin America. This revision makes it clear that the effects are going to be heterogeneous and that they could very well be costly. Therefore, public pol- icies aimed at reducing greenhouse gas emissions while at the same time promoting adaptive measures to climate change, are essential. The essay concludes with some considerations on future research topics that could contribute to the design of said public policies.